Pemberdayaan Panti Asuhan Berkah Palangka Raya sebagai Basis Usaha Olahan Ikan di Kota Palangka Raya Kalimantan Tengah: Empowerment of the Berkah Palangka Raya Orphanage as a Fish Processing Business Base in Palangka Raya, Central Kalimantan - Zubaidah, Siti; Norhayani, Norhayani; Rahayuningsih, Sri Endang Agustina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The Berkah Palangka Raya Orphanage is located on Jalan G. Obos Induk, Menteng, Jekan Raya. Students are directed to activities that can become provisions when they graduate from school and enter the community by introducing making processed fish nuggets, meatballs, and catfish sempol. The purpose of the activity is to improve the skills of the orphanage in making processed fish and to train entrepreneurship in processed fish. The action was carried out from August to November 2019. The method of activity was socialization, counseling, training, and fish processing. The questionnaire results before the activity showed that 40-90% of students were familiar with processed fish such as nuggets, sempol, and fish balls, but 90-100% did not know how to process them. After the activity, the questionnaire results showed that the orphanage already knew the ingredients for making and how to prepare nuggets, sempol, and fish balls. However, only 50-60% could correctly explain the stages of making nuggets, sempol, and fish balls. The most popular preparations are nuggets because they make it easy, practical, delicious, while others like fish balls because the taste is not much different from meatballs. As many as 90% of orphanage children are interested in entrepreneurship in the fish processing sector because they can make their own money and have a cooking hobby. It can be concluded that the orphanage children can make nuggets, sempol, and fish balls and give quite good results. Processed fish produced by orphanage children is quite tasty and in demand by consumers.